2016
DOI: 10.1038/srep20204
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and fungicidal activity of novel 2,5-disubstituted-1,3,4- thiadiazole derivatives containing 5-phenyl-2-furan

Abstract: A series of 2,5-disubstituted-1,3,4-thiadiazoles were synthesized using Lawesson’s reagent by an efficient approach under microwave irradiation in good yields. Their structures were characterized by MS, IR, 1H NMR, 13C NMR, and elemental analysis. Their in vitro and in vivo fungicidal activities revealed that the title compounds exhibited considerable activity against five selected fungi, especially to Phytophthora infestans. In order to illustrate the mechanism of title compounds against P. infestans, scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 43 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…12A-d) were formed in the mycelia. Much of the changes in mycelial appearance are probably due to the damage of the internal cell structure(53, 54). Next, our TEM results showed that the inhibited cell membranes were disrupted (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12A-d) were formed in the mycelia. Much of the changes in mycelial appearance are probably due to the damage of the internal cell structure(53, 54). Next, our TEM results showed that the inhibited cell membranes were disrupted (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, mycelia were fixed using 2.5% (v/v) glutaraldehyde (Solarbio, Beijing, China) for 24 h and dehydrated for 30 min in every step using aqueous ethanol solutions (30, 50, 70, and 90%, v/v). Then, morphological and surface changes were observed using an SEM system (JSM-7500F, JEOL, JAPAN)(53). A TEM (JEM-2100F, JEOL, JAPAN) system(53, 54) was also adopted to evaluate the structural characteristics of inhibited mycelia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro fungicidal activity against B. cinerea was tested using the mycelial growth inhibition method 48 . The tested compounds were dissolved in dimethyl sulfoxide (DMSO) and diluted with distilled water containing 0.05% Tween 80 to prepare the 10 mg/mL stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-two derivatives of 2,5-disubstituted-1,3,4-thiadiazole derivatives containing 5-phenyl-2-furan used in this work were taken from the literature [8]. The activity of the compounds were reported in EC50 (g/L) values, which were converted to pEC50 (pEC50 = − log1/EC50).…”
Section: Datasetmentioning
confidence: 99%